2020
DOI: 10.3389/fimmu.2020.591269
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation Induced During Interferon-α Therapy Impairs the Anti-HBV Immune Response Through CD24+CD38hi B Cells

Abstract: Type I interferon is widely used for antiviral therapy, yet has yielded disappointing results toward chronic HBV infection. Here we identify that PEG-IFNα-2b therapy toward persistent infection in humans is a double-edged sword of both immunostimulation and immunomodulation. Our studies of this randomised trial showed persistent PEG-IFNα-2b therapy induced large number of CD24+CD38hi B cells and launched a CD24+CD38hi B cells centered immunosuppressive response, including downregulating functions of T cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 47 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…PBMC of these patients were stimulated with HBsAg. 14,48 We found that the proportions of IFN-γ + CD8 + T cells and CD107a + CD8 + T cells were significantly increased at the +24 w timepoint, following IL-2 therapy initiation (Fig. 5b-d).…”
Section: Il-2 Therapy Increases the Expansion And Responses Of Hbvspecific Cd8 + T Cells In Nr (α-2b) Patients In Vivomentioning
confidence: 84%
See 1 more Smart Citation
“…PBMC of these patients were stimulated with HBsAg. 14,48 We found that the proportions of IFN-γ + CD8 + T cells and CD107a + CD8 + T cells were significantly increased at the +24 w timepoint, following IL-2 therapy initiation (Fig. 5b-d).…”
Section: Il-2 Therapy Increases the Expansion And Responses Of Hbvspecific Cd8 + T Cells In Nr (α-2b) Patients In Vivomentioning
confidence: 84%
“…13 What's more, we determined that IFN-α therapy for persistent HBV infection in humans may induce an immunomodulatory effect in chronic HBV patients by significantly upregulating levels of CD24 + CD38 hi B cells, which could drive an immunosuppressive program and reduce antiviral effects. 14 Suppressive mechanisms, such as the activity of regulatory T cells (Tregs) and programmed cell death protein 1 (PD-1) expression, have been demonstrated to occur during HBV infection. [15][16][17][18] However, the modulation of these inhibitory pathways in vitro has led to effective functional recovery in only a minority of patients with chronic hepatitis B (CHB).…”
Section: Introductionmentioning
confidence: 99%
“…IFN-I suppresses HBV replication when viral load is high and enhances HBV replication when viral load is low via transcriptional and post-transcriptional regulations ( Tian et al, 2011 ). However, some patients suffer from IFN-α treatment resistance by inducing CD24 + CD38 hi B cell and IFN-α/γ-STAT1-PD-L1 axis-mediated downregulating functions of T cells and NK cells ( Fu et al, 2020 ; Liu et al, 2020 ) as well as producing anti-IFN-α Abs ( Porres et al, 1989 ).…”
Section: Cytokines In Hepatitis B Virus Infectionmentioning
confidence: 99%
“…Pegylated interferon α‐2b initiates an immunosuppressive response centered on CD24 + CD38 hi B cells, including the downregulation of both T‐ and NK‐cell functions. Patients with low levels of CD24 + CD38 hi B cells were associated with improved therapeutic outcomes (Fu et al, 2020). In particular, the use of anti‐CD24 antibodies to deplete CD24 + CD38 hi B cells without compromising other B‐cell subsets suggests a promising strategy for improving therapeutic efficacy.…”
Section: Targeted Cd38 For B‐cell Diseasesmentioning
confidence: 99%
“…Pegylated interferon α-2b initiates an immunosuppressive response centered on CD24 + CD38 hi B cells, including the downregulation of both T-and NK-cell functions. Patients with low levels of CD24 + CD38 hi B cells were associated with improved therapeutic outcomes (Fu et al, 2020). In particular, the use of anti-CD24…”
Section: Disease Name Cd38 Expression Diagnosis and Prognosis Referencesmentioning
confidence: 99%